Methods of content – analysis of the Internet (Herald of Journalism, 2016)
The article is devoted to the transition process of traditional media to the Web. Discusses the causes of the media environment in KazNet . The examples of popular electronic media , discusses their advantages.
Keywords: new media; Internet; web